Growth, Yield and Seed Quality of Sunnhemp (Crotalaria juncea L.) as Influenced by Foliar Nutrition and Pinching - Mandal, S.; Dutta, A.; Bhattacharyya, P. K. (International Journal of Bio-resource and Stress Management, 2017)
Field experiment was conducted during rainy (Kharif) season of 2015 and 2016 to study the effects of pinching of terminal bud and foliar nutrition at flowering stage on Growth, yield and seed quality of Sunnhemp (Crotalaria juncea L.). Pinching of terminal bud when the plant attains a height of 90 cm in main plots and foliar nutrition at flowering stage in sub plots were studied in split plot design with four replications. The individual plant performance for growth parameters, seed yield and yield contributing parameters as well as total seed yield revealed that pinching of sunnhemp at a height of 90 cm in combination with foliar spray of DAP (2%)+Micro nutrient Spray (ZnSO4 @ 0.5%+Boric acid @ 0.3%)+NAA Spray (40 ppm) may be followed for obtaining high quantity and better quality seeds of sunnhemp. Effect of pinching and foliar nutrition on seed quality parameters revealed that seedling length was not significantly influenced by the pinching treatment while foliar applications had an effective role. Among different foliar applications, foliar spray of DAP (2%)+Micro nutrient Spray (ZnSO4 @ 0.5%+Boric Acid @ 0.3%)+NAA Spray (40 ppm) best results. Vigour index of the seedlings indicated that pinching treatment did not make any significant differences while foliar application of different treatments had a significant role.